Effects of COVID-19 pandemic on ART Service delivery: perspectives of healthcare workers in a Teaching Hospital in Ghana - Susanna Aba Abraham; Gifty Osei Berchie; Patience Fakornam Doe; Elizabeth Agyare; Stephen Ayisi Addo; Dorcas Obiri-Yeboah (BMC, 2021)
Abstract Background Ghana has a generalized HIV epidemic and efforts have been made to curb the spread and reverse its effects on the general population. In the wake of COVID-19 pandemic, the health system was unsettled and antiretroviral therapy (ART) care has been impacted in diverse ways. The study sought to explore the effects of COVID-19 on ART service provision in Ghana from the perspectives of the healthcare workers. Methods An exploratory-descriptive qualitative approach was employed in this study. Using maximum variation sampling method, fifteen healthcare workers; nurses, data managers and pharmacists were recruited from an ART clinic in a Teaching Hospital in Ghana. In-depth interviews were conducted and analysed using Braun and Clarke thematic approach. Results Three themes emerged from the data; "... And the pandemic struck", "Impact of the pandemic on ART service delivery"; "Effecting the needed change". The healthcare workers' initial reactions to the pandemic and their show of commitment in ensuring continued ART service was evident. COVID-19 impacted service delivery in three main ways; (1) clients' clinic attendance was erratic at various stages of the pandemic, (2) irregular resource availability as shortage was reported due to affected last mile delivery as a result of the lockdown in Accra, and (3) the health worker-patient interaction became less engaging because of established COVID-19 protocols. The healthcare workers however instituted strategies such as adjusting the patient appointment schedule, health professionals' work schedule, establishing several work stations, task-shifting, and ensuring the implementation of all the COVID-19 protocols within the ART unit to ensure consistent service delivery as well as patient and staff safety. The study also found a decline in the implementation of several strategies established in the ART clinic during the initial phases of the pandemic such as a decline in the supply of Personal Protective Equipment (PPEs) by hospital management. Conclusions Although several strategies were implemented to manage the effects of the pandemic on ART care, there is a need to establish pathways of support for healthcare workers within the ART clinic and to consolidate as well as institutionalise the changes that ensured continuous but safe service delivery.